(untitled) (Fiep Bulletin - online, 2011)
Introduction: Depression causes physical and psychological harm and negative consequences for the quality of life of affected individuals, thus justifying the conduct of study that seeks to know the prevalence, allowing more appropriate intervention in the diagnosis and treatment. Objective: To identify the prevalence of depressive symptoms in residents of institutions for the aged (RIA) and characterize the sociodemographic characteristics associated with depressive symptoms. Methodology: A descriptive and quantitative. To collect data we used the Brazilian version of the Geriatric Depression Scale containing 15 questions. The sample consisted of 26 elderly residents of three long-stay institutions for the elderly located in Natal /RN. Results: According to the score of the Geriatric Depression Scale, showed that 80% of elderly males had mild and female with 75%. The severe depression in males had no cases, however females had 6.3% of severe depression. Conclusion: This study showed a prevalence in both sexes, predominantly mild depression in males and the elderly above 71 years with more than a year of institutionalization. Thus, we suggest further studies to support the idea that the institutionalized elderly are more vulnerable to develop different types depression, requiring intervention that could help mitigate. For being considered a disease that affects humans in its entirety, without separation between the psychological, social and physical, the depression is a morbidity often undiagnosed, despite its relevance.